Detection rate of five respiratory pathogens before and during COVID-19 pandemic among ALRI hospitalizations of children aged 0 – 14 years at a tertiary children's hospital in Suzhou city, 2018 – July 2022 - Yingfeng LU; Jianmei TIAN; Tao ZHANG; Jian XUE; Xuejun SHAO; Genming ZHAO (Zhongguo gonggong weisheng, 2023)
ObjectiveTo analyze the variation in positivity rates of five respiratory pathogens before and during coronavirus disease 2019 (COVID-19) pandemic among 0 – 14 years old child inpatients with acute lower respiratory infection (ALRI) in Suzhou city for the prevention and treatment of ALRI in children. MethodsThe participants of the study were 9 005 children aged 0 – 14 years and hospitalized from 2018 through July 2022 due to ALRI (with discharge diagnosis codes of J09-J18 and J20-J22 of International Classification of Diseases, 10th Revision) at a tertiary children′s hospital of Suzhou city. We extracted the participants′ medical records and results of sputum specimen detection on respiratory syncytial virus (RSV), influenza virus A (FluA), influenza virus B (FluB), Streptococcus pneumoniae (Spn), and Haemophilus influenzae (Hi). The yearly and monthly detection rates of the five respiratory pathogens were described and compared to examine variations in the detection rates before (2018 – 2019) and during (2020 – July 2022) the COVID-19 pandemic. ResultsCompared to those in the same period of 2018 – 2019, the detection rate of FluA and FluB decreased significantly in 2020 (1.3% and 1.7%), 2021 (0.1% and 1.0%), and January – July of 2022 (3.5% and 3.2%) (all P < 0.05); there was no significant alteration in detection rate of RSV in 2020 (P > 0.05), but the detection rate was significantly higher in 2021 (20.8%) and in 2022 (18.9%) (both P < 0.05); the detection rate of Spn decreased significantly in 2020 (11.2%) and 2022 (8.9%) (both P < 0.05), while there was no significant change in the detection rate of Spn in 2021 (P > 0.05); significantly decreased detection rate of Hi was observed in 2020 (6.8%), 2021 (7.5%), and 2022 (4.0%) (all P < 0.05). In comparison to the average levels of non epidemic season, the monthly detection rate of RSV increased significantly to 13.9%, 9.2%, 28.8%, 43.5%, and 35.3% for the months of July – November, 2021 (P < 0.001 for all). Before 2020, the main co-infection detected was the infection of Hi and Spn or Flu, but in 2020, mainly detected co-infections were Hi plus Spn, Flu plus Hi, and RSV plus Spn; in 2021 and 2022, the main co-infection of RSV plus Spn was detected. There were differences in age group-specific detection rates of the five pathogens, with more RSV infections detected among the hospitalized children under one year of age, FluA or FluB infection in those age one year and over, and Spn or Hi infection in the hospitalized children under age of 6 years. ConclusionNon-pharmaceutical interventions on the COVID-19 pandemic could have a certain impact on detection rates of five common respiratory pathogens among 0 – 14 years old hospitalized children with ALRI in Suzhou city. The result suggests the necessity of pathogen surveillance in prevention and control of respiratory infections in children.